1993
DOI: 10.1002/bip.360330118
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular cyclization of (1 → 6)‐branched‐(1 → 3)‐β‐D‐glucans observed after denaturation–renaturation of the triple‐helical structure

Abstract: High molecular weight polysaccharide structure is conventionally described in terms of linear, comb-like, or treelike molecules. At a higher level of organization, various single-and multiple-stranded helical geometries have been described in addition to the less well-defined structures and connectivities that occur in noncovalently cross-linked gels. We report here on the finding of circular morphology in one type of high molecular weight multistranded polysaccharide. Circular structures have been described f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 18 publications
1
54
0
Order By: Relevance
“…Similar behavior was observed for scleroglucan [4] and schizophyllan [30]. However, it should be mentioned that, for the (1→3)(1→2)-β-D-Glucan, a great dispersion structure sizes was observed (scales are shown below each image), small linear and circular structures ( Figure 4a) coexisted with strands of 5 μm of length (Figure 4b) and small circular structures (Figure 4a) with rod-like linear strands (Figure 4c).…”
Section: Resultssupporting
confidence: 78%
“…Similar behavior was observed for scleroglucan [4] and schizophyllan [30]. However, it should be mentioned that, for the (1→3)(1→2)-β-D-Glucan, a great dispersion structure sizes was observed (scales are shown below each image), small linear and circular structures ( Figure 4a) coexisted with strands of 5 μm of length (Figure 4b) and small circular structures (Figure 4a) with rod-like linear strands (Figure 4c).…”
Section: Resultssupporting
confidence: 78%
“…Sato et al 36 and Yanaki et al 22 reported that the renaturation of denatured SPG chains involves two different molecular processes consisting of the collapse of random coil chains to more compact conformation by intrachain hydrogen bonding and the formation of aggregates by interchain hydrogen bonding. Additionally, Stokke et al, 30,31 McIntire et al, 13,32 and Kitamura et al 33 found that the DR treatment results in various DRSPG structures including globular, linear, and circular forms as well as more complicated multichain clusters. In the case of renaturation of partially denatured SPG aqueous solutions, an extended three-dimensional network is developed due to the imperfect registration between the chains forming triple helices.…”
Section: Rheological Measurementsmentioning
confidence: 96%
“…13,30 -34 By means of atomic force microscopy, electron microscopy, and gel permeation chromatography, Stokke et al, 30,31 McIntire et al, 13,32 and Kitamura et al 33 found that after DR treatment SPG exists in various forms such as globular, linear, and circular structures as well as more complicated multichain clusters. Vuppu et al 34 reported that the renaturation of partially denatured SPG chains leads to an extended network.…”
Section: Introductionmentioning
confidence: 97%
“…8,9 Our experiments have established that when the renaturation process is carried out in the presence of certain polynucleotides, the process creates a novel triple helix (the complex formation is schematically shown in Figure 2). In addition, it was also clarified that such complexation can occur commonly in water-soluble -1,3-glucan polysaccharides such as lentinan and laminaran.…”
Section: Yymentioning
confidence: 91%